Estimation of the effects of music therapy on the anxiety and patient’s perception during an upper gastrointestinal endoscopy procedure: a randomised controlled trial - Kannan, Vikram; Sundar, Sumathy; Prabhu, Sajeesh Manikanda; Ezhumalai, G. (International Journal of Research in Medical Sciences, 2020)
Background: An upper gastrointestinal (GI) endoscopy procedure is an invasive medical procedure that is used in diagnosis and treatment of various intestinal disorders. Patients posted for upper GI endoscopy procedures often experience significant levels of pre-procedural fear, anxiety and discomfort during the procedure which can negatively affect cooperation levels during the procedure with the attending doctor. A very few studies have explored the beneficial effects of music therapy in this regard and so our study was planned. Methods: A prospective randomised controlled trial was conducted with a sample of 54 patients who were enrolled for this study. They were randomly divided into two groups - group 1 consisting of 27 patients, receiving a music therapy intervention and group 2 consisting of 27 patients who served as a control group. Group 1 received a receptive music therapy intervention in the form vocal, relaxing, improvisational music with patient preferred chants for fifteen minutes before and during the endoscopy procedure. Group 2 did not receive a music therapy intervention. Results: The results indicated that the post intervention, state-anxiety levels was significantly lower in the music therapy group compared to the control group with (p=0.001). Patients’ cooperation levels during the procedure with the attending doctor was significantly higher in the music therapy group than in the control group (p=0.001). Conclusions: Repeated music therapy intervention is highly beneficial in reducing state anxiety levels and improving cooperation levels during the GI endoscopy procedure.